Comparative Assessment of Anti-HLA Antibodies Using Two Commercially Available Luminex-Based Assays. Issue 11 (November 2017) - Clerkin, Kevin J.; See, Sarah B.; Farr, Maryjane A.; Restaino, Susan W.; Serban, Geo; Latif, Farhana; Li, Lingzhi; Colombo, Paolo C.; Vlad, George; Ray, Bryan; Vasilescu, Elena R.; Zorn, Emmanuel
Abstract : Background: Allospecific anti-HLA antibodies (Abs) are associated with rejection of solid organ grafts. The 2 main kits to detect anti-HLA Ab in patient serum are commercialized by Immucor and One Lambda/ThermoFisher. We sought to compare the performance of both platforms. Methods: Background-adjusted mean fluorescence intensity (MFI) values were used from both platforms to compare sera collected from 125 pretransplant and posttransplant heart and lung transplant recipients. Results: Most HLA class I (94.5%) and HLA class II (89%) Abs with moderate to high MFI titer (≥4000) were detected by both assays. A modest correlation was observed between MFI values obtained from the 2 assays for both class I ( r = 0.3, r 2 = 0.09, P < 0.0001) and class II Ab ( r = 0.707, r 2 = 0.5, P < 0.0001). Both assays detected anti–class I and II Ab that the other did not; however, no specific HLA allele was detected preferentially by either of the 2 assays. For a limited number of discrepant sera, dilution resulted in comparable reactivity profiles between the 2 platforms. Conclusions: Immucor and One Lambda/ThermoFisher assays have a similar, albeit nonidentical, ability to detect anti-HLA Ab. Although the correlation between the assays was present, significant variances exist, some of which can be explained by a dilution-sensitive "prozone" effect. Abstract : Supplemental digital content is available in the text.